Student Development in Higher Education in the Era of the Agenda 2030 and the UN's Sustainable Development Goals: Towards SDGs 2.0. Issue 1 (2nd January 2023) - Schreiber, Birgit; Torabian, Juliette
Abstract: The UN Educational, Scientific and Cultural Organization (UNESCO) World Higher Education Conference in Barcelona was an occasion for the authors of this article to reflect on the UN Sustainable Development Goals (SDGs) in general and SDG 4: education, specifically, pondering over its role and impact on student development in the Global South and North. The authors are indeed glad that UNESCO is taking the initiative to revitalize the role of higher education in sustainable development. But the authors are also concerned and question the extent to which higher education institutions (HEIs) are enabled and encouraged by the discourse of the 2030 Agenda to contribute toward the achievement of the SDGs and the type of challenges they may encounter, particularly with regard to developing students' capacities as global and engaged citizens within the boundaries of the SDGs and SDG 4.